2012
DOI: 10.1371/journal.pone.0032920
|View full text |Cite
|
Sign up to set email alerts
|

Folate Decorated Dual Drug Loaded Nanoparticle: Role of Curcumin in Enhancing Therapeutic Potential of Nutlin-3a by Reversing Multidrug Resistance

Abstract: Retinoblastoma is the most common intraocular tumor in children. Malfunctioning of many signaling pathways regulating cell survival or apoptosis, make the disease more vulnerable. Notably, resistance to chemotherapy mediated by MRP-1, lung-resistance protein (LRP) is the most challenging aspect to treat this disease. Presently, much attention has been given to the recently developed anticancer drug nutlin-3a because of its non-genotoxic nature and potency to activate tumor suppressor protein p53. However, bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(56 citation statements)
references
References 53 publications
3
52
1
Order By: Relevance
“…Third, NP loaded with Nutlin-3 exhibited good drug content (at about 5 mg/100 mg of formulation) and encapsulation efficiency (close to 50%). This percentage is lower with respect to that reported by previous authors (8,9) and is likely a consequence of the repeated centrifugation required to purify the samples especially both from PVA and from the reagents used during the coupling with antibody. Finally, NP-Nut and NP-Rt-Nut were able to functionally activate the p53 pathway in vitro, as also shown by the induction of cell-cycle arrest and of apoptosis in JVM-2 cells.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Third, NP loaded with Nutlin-3 exhibited good drug content (at about 5 mg/100 mg of formulation) and encapsulation efficiency (close to 50%). This percentage is lower with respect to that reported by previous authors (8,9) and is likely a consequence of the repeated centrifugation required to purify the samples especially both from PVA and from the reagents used during the coupling with antibody. Finally, NP-Nut and NP-Rt-Nut were able to functionally activate the p53 pathway in vitro, as also shown by the induction of cell-cycle arrest and of apoptosis in JVM-2 cells.…”
Section: Discussioncontrasting
confidence: 68%
“…The studies conducted so far by our and other groups of investigators have strongly suggested that the preclinical evaluation of Nutlin-3 appears highly warranted (2, 3). Interestingly, to overcome the potential problems related to the poor solubility of Nutlin-3, it has been proposed to use PLGA NPs, which showed improved delivery and efficacy of Nutlin-3 in vitro in solid tumor cell models (8,9). However, to the best of our knowledge, NPs loaded with Nutlin-3 have never been examined in animal models before the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The same higher competency of nanocurcumin was seen in reversal of lead-induced altered biochemical parameters (ROS, GSH, and TBARS) indicative of oxidative stress in the kidney, brain, and liver [96]. Nanocurcumin has shown signs of overcoming the multidrug resistance that commonly arises on administration of various ranges of typical and novel chemotherapeutic agents that proves to be a major bottleneck in the treatment of many diseases, particularly cancer [97][98][99]. Coating of nanocurcumin by polymer will shield if opposed to degradation by light and warmth.…”
Section: Removal Of Lead Toxicity By Nanocurcuminmentioning
confidence: 95%
“…It was reported that the application of nutlin-3 and curcumin in nanoparticles results in the modulation of efflux proteins by curcumin, and thus results in an increase in nutlin-3 function. The outcome of these events reverses multidrug resistance in Y79 human retinoblastoma cell lines (Das & Sahoo, 2012). Benzodiazepinedione (BDA) is also a powerful molecule in recognizing the p53-binding domain of Mdm2 (Grasberger et al, 2005).…”
Section: Prevention Of Apoptosismentioning
confidence: 99%